PERTANGGUNGJAWABAN NOTARIS TERHADAP COVERNOTE YANG DIBUATNYA DALAM PERJANJIAN KREDIT - Arizona, Renanda; Sinaulan, Ramlani Lina; Kencanawati, Erny (SENTRI: Jurnal Riset Ilmiah, 2023)
The use of notary covernotes in credit agreements can cause bank losses in the event of default while the process of binding mortgage rights has not been completed. This study raised two formulations of the problem, namely how the legal consequences of the use of cover notes on credit agreements? and what about the legal responsibility of Notaries related covernote in credit agreements?, using the theory of legal consequences and the theory of professional ethics of notaries. The method used in this study with this type of research juridical normative legal research literature or secondary data with sources of legal materials primary, secondary, tertiary and supported interview. The research approach used is legal approach, case approach, conceptual approach and analytical approach. Legal material collection techniques performed by identifying and intervening in the rule of Law positive, literature books, journals and other sources of legal materials. For technical analysis legal material is carried out by the interpretation of grammatical laws and methods construction of a legal analogy. The results showed that the legality of Covernote cannot be considered as an authentic deed in accordance with the authority of notary officials in making authentic deeds, because Covernote does not meet the requirements set forth in Article 1868 of the Civil Code. Covernote is not part of the law provided for in the law, it is only a practice or custom that develops in the performance of Notarial duties. The factors that encourage a notary to issue a Covernote are usually related to the unfinished work related to the duties and authority of the notary to issue an authentic deed. Covernote is used as a notification that the customer's land letters of credit application are still in the process of certification, royalty process, reverse name, or breakdown process if they have been certified. For example, in the application for a credit agreement, application for a building permit (IMB), application for a decree of the Ministry of Law and Human Rights (Kemenkumham), management of Rights applications, and others. The notary's responsibility related to the Covernote he made is related to the Supreme Court decision number 181/PDT/2019/PT MKS. The notary is responsible in the event that the Covernote is not implemented in accordance with the contents of the Covernote, and the notary may be subject to civil penalties in the form of reimbursement of costs, damages, and interest due to which the notary must pay to the party who suffered losses due to the violation. This is a form of Notarial responsibility in compensating for losses suffered by the injured party